Observación desde los umbrales - Vela Vargas, Paola (2023)
This visual essay is based on Walter Benjamin’s critical analysis of the model of perceptual experience inaugurated by industrial culture, which influenced the observation and understanding of reality and the production of images of the avantgarde movements of the 20th century. In this way, the photographs selected have been recorded over several years with the aim of recovering the experience of observation from the thresholds, which are understood as interstices between the public and the private, between outside and inside, between the past and the present. The final objective of this essay is to recover a contemplative spectator that from a “middle” space, can represent the decline of urban spaces built thanks to the triumph of capital and the circulation of commodities.